PENENTUAN TIPOLOGI AKIFER BERDASARKAN METODA GEOLISTRIK DAN HIDROKIMIA, KOTA TANGERANG - Dwi Hadian, M. Sapari (Fakultas Teknik Geologi Universitas Padjadjaran, 2005)
Electrical sounding expectation is used to estimate the early model from a groundwater system in thefield, which can be used as a comparison of field results. The comparison enhances to entrust the processof field activities and provide the opportunity to modify the programs in the field and to ensure that we haveenough information received efficiently - in a point of view of geological framework. A Usefulness of amapping hydrogeology is to show the under surface geometry (structure) and the hydraulic property fromearth materials which is used to investigate the hydrodynamic property appeared from the undergroundwater on natural shares ( Basin) or a part of its filler.The exploration using the method of the electrical sounding is conducted on land surface by injecting adirectional current (DC) with a low frequency into a deeper ground passing through two current electrodes.A different potential capacity is measured on the surface by two potential electrodes. The result of themeasurement capacity which is injected and the potential difference occurred in every different electrodedistance will give a value variation of a typical resistance. The value variation shows the existence of anunderground rock coat variation, while the method of hydrochemistry explains the genesis of thegroundwater based on a physical characteristic and chemistry substances on the field.Both methods are expected to reconstruct the aquifer condition and its system through surface andunderground surveys. The combination results of both surveys must be depicted in a form of ahydrogeology map (and its differential map), a block diagram depicting the aquifer, and aquifer system ina form of two dimensions. The other surface hydrogeology surveys use geological method. In contrast, theunderground hydrogeology survey use the electrical sounding method.